IFRS adoption in China and foreign institutional investments - Mark L. DeFond; Xinzi Gao; Oliver Zhen Li; Lijun Xia (China Journal of Accounting Research, 2019)
We examine the effectiveness of China's IFRS adoption from the perspective of an important set of financial report users, foreign institutional investors. We find that foreign institutional investment does not increase after China's IFRS adoption, and some evidence that it actually declines, particularly among firms with weaker incentives to credibly implement IFRS, or with greater ability to manipulate IFRS's fair value provisions. We also find that the association between earnings and returns generally declines after IFRS adoption, consistent with reduced earnings quality. In addition, we find that foreign institutional investors' returns decrease after China's IFRS adoption. Finally, the decline in foreign institutional investment is greater among investors from countries with weak institutions that have also adopted IFRS. Taken together, our evidence suggests that the weak institutional infrastructure in China's transitional economy impairs IFRS's intended goal of attracting institutional investment through improved financial reporting quality. Further, financial information users' home country institutions and IFRS adoption experience affect the effectiveness of IFRS adoption.
Keywords: 650; China; Institutions; Foreign institutional investment; IFRS